The Effect Of Good Corporate Governance On Tax Avoidance In Manufacturing Companies (Idx Empirical Study) Period 2017 –2021 - Primas Syahroul Asprila Afandi; Ibnu Fajarudin (Journal of World Conference (JWC), 2023)
The purpose of this study is to identify and analyze the influence of company characteristics or Good Corporate Governance which is proxied to be institutional ownership, the percentage of independent commissioners, the number of commissioners, the role of audit committees, audit quality, and fiscal loss compensation on tax avoidance in manufacturing sector companies. industries listed on the Indonesia Stock Exchange in 2017-2021. This research uses quantitative methods. The population in this study consists of industrial sector manufacturing companies listed on the IDX for the 2017-2021 period. The sampling method used in this study was purposive sampling of 17 companies. The data collection method uses the documentation method and uses secondary data in the form of company annual reports with samples obtained through the official website of the Indonesia Stock Exchange, namely www.idx.co.id. This study was analyzed using multiple linear regression analysis. Based on the results of the research that has been done, it can be concluded that institutional ownership, the number of commissioners, fiscal loss compensation has no significant effect on tax evasion, and the percentage of commissioners has no significant effect on tax evasion, while the audit committee, audit quality has a significant effect on tax evasion in industrial sector manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2021 period.